Cognitive safety of focused ultrasound thalamotomy for tremor: 1-year follow-up results of the COGNIFUS part 2 study - Saporito, Gennaro; Sucapane, Patrizia; Bruno, Federico; Catalucci, Alessia; Masciocchi, Carlo; Pistoia, Maria Letizia; Splendiani, Alessandra; Ricci, Alessandro; Di Cesare, Ernesto; Marini, Carmine; Mazza, Monica; Totaro, Rocco; et al. (Frontiers in Neurology, 2024)
Introduction In the COGNitive in Focused UltraSound (COGNIFUS) study, we examined the 6-month cognitive outcomes of patients undergoing MRgFUS thalamotomy. This study endorsed the safety profile of the procedure in terms of cognitive functions that cannot be evaluated in real-time during the procedure unlike other aspects. The aim of the COGNIFUS Part 2 study was to investigate the cognitive trajectory of MRgFUS patients over a 1-year period, in order to confirm long-term safety and satisfaction. Methods We prospectively evaluated the cognitive and neurobehavioral profile of patients with essential tremor (ET) or Parkinson’s Disease (PD) related tremor undergoing MRgFUS thalamotomy at 1 year-follow-up following the treatment. Results The sample consists of 50 patients (male 76%; mean age ± SD 69.0 ± 8.56; mean disease duration ± SD 12.13 ± 12.59; ET 28, PD 22 patients). A significant improvement was detected at the 1 year-follow-up assessment in anxiety and mood feelings (Hamilton Anxiety rating scale 5.66 ± 5.02 vs. 2.69 ± 3.76, p ≤ <0.001; Beck depression Inventory II score 3.74 ± 3.80 vs. 1.80 ± 2.78, p = 0.001), memory domains (Rey Auditory Verbal Learning Test, immediate recall 31.76 ± 7.60 vs. 35.38 ± 7.72, p = 0.001 and delayed recall scores 5.57 ± 2 0.75 vs. 6.41 ± 2.48), frontal functions (Frontal Assessment Battery score 14.24 ± 3.04 vs. 15.16 ± 2.74) and in quality of life (Quality of life in Essential Tremor Questionnaire 35.00 ± 12.08 vs. 9.03 ± 10.64, p ≤ 0.001 and PD Questionnaire −8 7.86 ± 3.10 vs. 3.09 ± 2.29, p ≤ 0.001). Conclusion Our study supports the long-term efficacy and cognitive safety of MRgFUS treatment for ET and PD.